Bioethics and Contemporary Art: Examples and Questions - Παπαδάκη (Niovi - Evgenia Papadaki) Νιόβη - Ευγενία (Bioethica, 2015)
The aim of this essay is to portray the common paths of art and science from the aspect of bioethics. At first sight such a combination seems incompatible. However, in the process of approaching contemporary art, a series of concerns and questions emerge with regard to bioethics. Within this framework, examples of living organisms, animals, but also human bodies used in contemporary art, are presented. Through these examples bioethical issues are illustrated and positions in favor or against combining art and science are concluded.